Analysis of Marketing Mix and Tourist Attraction on Visit Interest of Domestic Tourists to Lolai Negeri Di Atas Awan - Paulus Palimbong; Sapar Sapar (Quantitative Economics and Management Studies, 2022)
This study aims to analyze and describe the Marketing Mix variable and the Domestic Attractiveness Negeri di Atas Awan – Lolai, Toraja on the interest of domestic tourists to visit. The data collection technique is by distributing questionnaires to respondents who have visited Negeri di Atas Awan and assessing the tourist attractiveness of the destination. The sampling technique is non-probability sampling with an accidental approach. The results of this study indicate that the marketing mix affects the interest of domestic tourists visiting by 0.428 units with a calculated T value of 3.285 > T table of 1.660. Tourist attraction affects the interest of domestic tourists to visit because the regression coefficient value is 0.388 with the calculated T value of 2.965 > T table of 1.660. Overall. The influence of the marketing mix and tourist attraction on the interest of domestic tourists to visit is 61.7%, and other factors influence the remaining 38.3%.